Study On The Cross Compatibility Of Some Lemon Genotypes (Citrus Limon L.) (Bangladesh Journal of Agricultural Research, 2011)
An investigation was carried out at the Department of Horticulture, Bangladesh Agricultural University, Mymensingh to examine compatible relationship among the available lemon genotypes. Seven selected genotypes of lemon were used for hybridization. Crossings were performed following diallel fashion. The results revealed that the lower percentage of fruit setting as well as seed setting in some cross combinations noticed the existence of incompatibility among the selected genotypes. The percentages of fruit setting and seed setting were higher in the cross-pollination than in the self- pollination, which was an indication of self-incompatibility. To achieve seedless fruit setting, self-incompatibility may be used successfully. Keywords: Cross compatibility; lemon genotypes. DOI: http://dx.doi.org/10.3329/bjar.v36i2.9250 BJAR 2011; 36(2): 241-246